Battery‐Free, Wireless, Ionic Liquid Sensor Arrays to Monitor Pressure and Temperature of Patients in Bed and Wheelchair. Issue 9 (19th December 2022) - Han, Hyeonseok; Oh, Yong Suk; Cho, Seokjoo; Park, Hyunwoo; Lee, Sung‐Uk; Ko, Kabseok; Park, Jae‐Man; Choi, Jungrak; Ha, Ji‐Hwan; Han, Chankyu; Zhao, Zichen; Liu, Zhuangjian; et al.
Abstract: Repositioning is a common guideline for the prevention of pressure injuries of bedridden or wheelchair patients. However, frequent repositioning could deteriorate the quality of patient's life and induce secondary injuries. This paper introduces a method for continuous multi‐site monitoring of pressure and temperature distribution from strategically deployed sensor arrays at skin interfaces via battery‐free, wireless ionic liquid pressure sensors. The wirelessly delivered power enables stable operation of the ionic liquid pressure sensor, which shows enhanced sensitivity, negligible hysteresis, high linearity and cyclic stability over relevant pressure range. The experimental investigations of the wireless devices, verified by numerical simulation of the key responses, support capabilities for real‐time, continuous, long‐term monitoring of the pressure and temperature distribution from multiple sensor arrays. Clinical trials on two hemiplegic patients confined on bed or wheelchair integrated with the system demonstrate the feasibility of sensor arrays for a decrease in pressure and temperature distribution under minimal repositioning. Abstract : This paper introduces a method for real‐time, continuous multi‐site monitoring and mapping of pressure and temperature distribution from strategically deployed sensor arrays at skin interfaces through battery‐free, wireless ionic liquid pressure sensors for prevention of pressure injuries of bedridden or wheelchair patients.